Феномен мультимодальності в коміксах (на матеріалі англійської мови) - Івасишин, М. Р.; Івасишин, Маріанна Романівна; Ivasyshyn, Marianna; Ivasyshyn, M. R. (Одеса, 2017)
У статті розглядається феномен мультимодальності та вербальні й невербальні засоби його експлікації на матеріалі англомовного коміксу. За допомогою елементів мультимодальності здійснюється тлумачення отриманої з тексту інформації. У статті висвітлено основні рівні мультимодальності тексту - часткову та повну мультимодальність. Явище мультимодальності висвітлюється на матеріалі коміксу «Captain America».

The article presents the phenomenon of multimodality and the means of its realization in English-language comics. These means are represented by verbal and non-verbal components. These components improve the reader’s comprehension of the information presented in the text. The author highlights two levels of multimodality in the text. These levels are presented by complete or partial creolization. On the basis on "Captain America" comic book, the article reveals the phenomenon of creolization.
Івасишин М. Р. Феномен мультимодальності в коміксах (на матеріалі англійської мови) / М. Р. Івасишин // Одеський лінгвістичний вісник. – 2017. – Вип. 9. – Т.1. – С. 75-79.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; модальність; мультимодальність; мультимодальний текст; семіотична система; повна мультимодальність; часткова мультимодальність; modality; multimodality; multimodal text; semiotic system; complete creolization; partial creolization